Ophthalmological findings in children with non-syndromic craniosynostosis: preoperatively and postoperatively up to 12 months after surgery. Issue 1 (26th April 2021) - Ntoula, Evangelia; Nowinski, Daniel; Holmstrom, Gerd; Larsson, Eva
Abstract : Aims: Craniosynostosis is a congenital condition characterised by premature fusion of one or more cranial sutures. The aim of this study was to analyse ophthalmic function before and after cranial surgery, in children with various types of non-syndromic craniosynostosis. Methods: Children referred to Uppsala University Hospital for surgery of non-syndromic craniosynostosis were examined preoperatively. Visual acuity was measured with Preferential Looking tests or observation of fixation and following. Strabismus and eye motility were noted. Refraction was measured in cycloplegia and funduscopy was performed. Follow-up examinations were performed 6–12 months postoperatively at the children's local hospitals. Results: One hundred twenty-two children with mean age 6.2 months were examined preoperatively. Refractive values were similar between the different subtypes of craniosynostosis, except for astigmatism anisometropia which was more common in unicoronal craniosynostosis. Strabismus was found in seven children, of which four had unicoronal craniosynostosis. Postoperatively, 113 children were examined, at mean age 15.9 months. The refractive values decreased, except for astigmatism and anisometropia in unicoronal craniosynostosis. Strabismus remained in unicoronal craniosynostosis. Two new cases with strabismus developed in unicoronal craniosynostosis and one in metopic, all operated with fronto-orbital techniques. No child had disc oedema or pale discs preoperatively or postoperatively. Conclusion: Ophthalmic dysfunctions were not frequent in children with sagittal craniosynostosis and preoperative ophthalmological evaluation may not be imperative. Children with unicoronal craniosynostosis had the highest prevalence of strabismus and anisometropia. Fronto-orbital techniques used to address skull deformity may be related to a higher prevalence of strabismus postoperatively.